Village-Owned Enterprises Legal Accountability for Village Natural Resources Management in the Perspective of Separate Legal Entity and Legal Certainty - Naili Hidayah, Lili; Najwan, Johni; Suryahartati, Dwi (Fakultas Hukum Universitas Jambi, 2025)
This article examines the construction of legal accountability for the management of natural resource-based village assets by Village-Owned Enterprises (BUMDesa) after its recognition as a legal entity through Government Regulation Number 11 of 2021. This recognition places BUMDesa as an independent legal subject that operates based on the principle of separate legal entity. However, in practice, the application of this principle still leaves juridical problems, especially related to the separation between village wealth and BUMDesa wealth and the potential shift in the character of village assets from public wealth to objects of private interest. This condition has implications for the weakening of legal protection for village assets and the increased risk of irregularities in the management of village natural resources. This article emphasizes that the legal accountability of BUMDes is dualistic, namely corporate responsibility for business activities and public accountability for the protection of the interests of village communities and the sustainability of natural resources. The absence of a firm and systematic regulation causes a legal gray space that blurs the boundaries of responsibility between BUMDesa and the village government. Therefore, it is necessary to reconstruct the regulation and strengthening of BUMDesa governance to ensure legal certainty, maintain the public character of village assets, and ensure that its use remains in line with the constitutional goals of maximum prosperity of the people